2011
DOI: 10.1038/ja.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Phthalide derivatives with antifungal activities against the plant pathogens isolated from the liquid culture of Pestalotiopsis photiniae

Abstract: Three new phthalide derivatives (1-3) named 5-(3¢-methyl-2¢-butenyl)-2-hydroxy-3-methoxy-4-methylbenzoic acid (1), 5-(3¢-carboxyl-3¢-methyl-2E-allyloxy)-3-methoxy-4-methylphthalide (2) and 5-(3¢,3¢-dimethylallyloxy)-2-methoxycarbonyl-3-methoxy-4-methylbenzoic acid (3) together with six known phthalide derivatives named 5-(3¢,3¢-dimethylallyloxy)-3-methoxy-4-methylphthalide (4), zinnimidine (5), 5-(3¢,3¢-dimethylallyloxy)-3-methoxy-4-methylphthalide (6), 5-(3¢,3¢-dimethylallyloxy)-3-methoxy-4-methylphthalic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Until 2005, approximately 180 naturally occurring phthalides had been isolated, most of them from the Apiaceae family . Compounds containing γ –lactone, particularly naturally occurring phthalides and their synthetic analogues, exhibit not only a variety of pharmacological but also phytotoxic, fungicidal and insecticidal activities . Some of these molecules are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2005, approximately 180 naturally occurring phthalides had been isolated, most of them from the Apiaceae family . Compounds containing γ –lactone, particularly naturally occurring phthalides and their synthetic analogues, exhibit not only a variety of pharmacological but also phytotoxic, fungicidal and insecticidal activities . Some of these molecules are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations reported that the destruction of the bacterial cell might be the possible antifungal activity of compounds isolated from the Pestalotiopsis sp. [23,24]. In this study, we found that the endophytic fungus Pestalotiopsis sp.…”
Section: Resultsmentioning
confidence: 84%
“…MP was provided by our research group at Hebei University (purity >99%, HPLC analysis) (7) and dissolved in DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…MP was first isolated from Alternaria porri and reported to have antifungal activity and cytotoxic activity in cancer cell lines 9 (5- 7). Although cytotoxic activity of MP was reported, little was known about the molecular mechanism of this effect of MP.…”
Section: Introductionmentioning
confidence: 99%